2016
DOI: 10.1039/c5ee03315b
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient, large area, roll coated flexible and rigid OPV modules with geometric fill factors up to 98.5% processed with commercially available materials

Abstract: Flexible roll-coated and rigid organic PV modules, solution processed on a large area, are reported with efficiencies of 4.2% and 5.3%, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
124
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(125 citation statements)
references
References 25 publications
1
124
0
Order By: Relevance
“…A key difference between the batch and roll-to-roll processes is the time constraint in the roll-to-roll process. [34,37,39,40,42,[78][79][80][81][82] We found the record PCEs of slot-die coated PSCs have been surprisingly low, as shown in Figure 5d. Therefore, time-consuming processes, such as solvent soaking technique, cannot be used in the roll-to-roll process.…”
mentioning
confidence: 78%
See 1 more Smart Citation
“…A key difference between the batch and roll-to-roll processes is the time constraint in the roll-to-roll process. [34,37,39,40,42,[78][79][80][81][82] We found the record PCEs of slot-die coated PSCs have been surprisingly low, as shown in Figure 5d. Therefore, time-consuming processes, such as solvent soaking technique, cannot be used in the roll-to-roll process.…”
mentioning
confidence: 78%
“…[31][32][33][34][35] For example, Yan and co-workers showed that blade-coated PSCs with PffBT4T-2OD:PC 71 BM based BHJ can produce a high PCE of up to 9.9%. [37][38][39] However, the slot-die method has not been well studied and the efficiency of slot-die based devices has still remained low, compared to the high PSCs in the recent reported spin-coating based PSCs. [31] In particular, 12.88% PCE was achieved in doctor blade-coated PBDB-TF:IT-4F PSCs through controlling the surface morphology of the ZnO interlayer; [36] and more recently, Hou and co-workers demonstrated a top efficiency of 13.1% from the blade-coated PSCs based on T1:IT-4F.…”
mentioning
confidence: 99%
“…37 On top of IMI, we processed commercial ZnO nanoparticles (Nanograde) as the electron selective electrode. As a photoactive layer we coated a medium band gap conjugated polymer PBTZTstat-BDTT-8 38,39 (Fig. S1, ESI †) blended with phenyl-C61-butyric acid methyl ester [60]PCBM on top of ZnO (see Materials and methods for details).…”
Section: Laminated Solar Cellsmentioning
confidence: 99%
“…around 8 cm width and greater). Nevertheless, the highest module efficiencies are around 5.3% for rigid modules and around 5% for flexible modules on a large scale . Generally the literature would cite 10% efficiency as the goal for such devices, but recent experience has shown that, due to their additional qualities such as variable colours and adaptability to building aesthetics and needs, lower efficiencies are acceptable .…”
Section: Introductionmentioning
confidence: 99%